Anemic retinopathy as the presenting symptom of a mediastinal germ cell tumor - Christian Tallo; Paul Farris; Edmund Farris (American Journal of Ophthalmology Case Reports, 2025)
Purpose: To describe a rare case of anemic retinopathy as the initial presenting symptom of a mediastinal germ cell tumor. Observations: A 27-year-old male with no prior medical history presented with a one-day history of central vision loss in his left eye. Funduscopic evaluation showed a central macular hemorrhage in the left eye and bilateral nerve fiber layer hemorrhages and blot hemorrhages. Fluorescein angiography showed multiple hemorrhages without vascular occlusion or neovascularization, features indicative of anemic retinopathy. Laboratory evaluation demonstrated severe anemia (hemoglobin 6.7 g/dL), with an otherwise unremarkable metabolic and coagulation profile. Given these findings, an underlying hematologic or oncologic disorder was suspected, prompting further systemic evaluation. Imaging revealed a large anterior mediastinal mass, and biopsy confirmed a nonseminomatous germ cell tumor. The patient underwent chemotherapy with cisplatin, etoposide, and bleomycin, later transitioning to VIP (ifosfamide, etoposide, and cisplatin) due to suspected pulmonary toxicity. Patient responded well to treatment; his anemia gradually improved, and alpha-fetoprotein levels significantly declined. Following treatment, the patient reported no ongoing visual disturbances. Conclusions and importance: Anemic retinopathy can be the initial presentation of an underlying malignancy. Recognizing ophthalmologic findings as potential indicators of systemic disease is critical for early diagnosis and timely intervention in cases of occult malignancies.